P05 What are the signs and symptoms of bone tumours in childhood? are the great british public aware of them?. (25th October 2020) - Shanmugavadivel, D; Liu, JF; Stewart, A; Gamble, A; Walker, D
Abstract : Aims: Bone tumours in children/young people are often associated with significant diagnostic delay, increasing the risk of amputation. The total diagnostic interval is a sum total of the patient and system interval. The HeadSmart campaign showed a national awareness campaign based on high quality evidenced based guidance halved time to diagnosis. We conducted a systematic review and meta-analysis to identify the core signs/symptoms and a public survey to understand public awareness of these symptoms. Methods: Medline, Pubmed and Embase databases were searched from January 2005 – August 2015. Key words included 'bone tumour(s)', 'bone neoplasm(s)', 'diagnosis', 'signs(s)', 'symptom(s)', 'presentation(s)'. All papers discussing bone tumour presentation were included. Pooled proportions (%) of children with each sign/symptom at diagnosis were estimated. A face-to-face opinion survey (n=1000; 475 males) was conducted by Ipsos MORI. Questions included perception of cancer risk, confidence in recognising signs/symptoms and urgency of seeking medical advice. Results: The search strategy identified 15477 papers. 713 papers were reviewed in full; 11 met the inclusion criteria, describing the symptoms/signs at diagnosis in 1246 children. 29 symptoms/signs were recorded but only those that occurred in 2% or more of patients are reported. These were pain (76%), swelling (21%), fever (4%), history of trauma (3%), functional limitation (3%), palpable mass (3%), pain and swelling (2%), volume increase (2%), limp (2%) and pathological fracture (2%). Public awareness of the top 4 presenting symptoms of bone tumours were low. 23% of the public identified recurrent or persistent bone pain as a symptom of cancer; 27% identified swelling of bone or joint; 21% identified fever and 14% thought a slow recovery after injury or trauma could be a sign of cancer. Conclusions: This is the first systematic review on paediatric bone tumours to our knowledge. It provides strong evidence of the common presentations and will form the basis of a new RCPCH endorsed clinical guideline on the assessment/investigation of suspected bone tumours. The results of the public awareness survey highlight low awareness which need to be tackled in order to drive earlier diagnosis. This will form key messaging in our new national awareness campaign called ChildCancerSmart.